Development of a plasma- and albumin -free recombinant von Willebrand factor - Turecek, P. L.; Mitterer, A.; Matthiessen, H. P.; Gritsch, H.; Varadi, K.; Siekmann, J.; Schnecker, K.; Plaimauer, B.; Kaliwoda, M.; Purtscher, M.; Woehrer, W.; Mundt, W.; Muchitsch, E.-M.; Suiter, T.; Ewenstein, B. M.; Ehrlich, H. J.; Schwarz, H. P. (Hämostaseologie, 2009)
Baxter has developed a recombinant therapy for treating von Willebrand‘s disease. Recombinant VWF is co-expressed with the rFVIII in CHO cells used to produce the rFVIII product Advate. This rVWF is used as a drug component for a rVWF-rFVIII complex drug product. CHO cells produce partially processed and partially un-processed rVWF still containing the pro-peptide. In order to make a consistent preparation containing mature and processed rVWF only, rVWF is exposed to recombinant furin to remove the pro-peptide. Recombinant VWF and furin are produced under serum- and protein-free conditions. It is highly purified by a series of chromatographic steps and formulated in a protein-free buffer and has a homogeneous multimer distribution. The specific activity is higher in rVWF than in commercial plasma-derived VWF-FVIII complex products. SDS agarose electrophoretic analysis shows the presence of ultra-high molecular weight multimers. The FVIII-binding capacity and affinity of rVWF to FVIII is comparable to VWF in plasma. Carbohydrate analysis shows an intact glycosylation pattern. Recombinant VWF binds to collagen and promotes platelet adhesion under shear stress. It stabilizes endogenous FVIII in VWF-deficient knock-out mice as seen by a secondary rise in murine FVIII.
Keywords: Recombinant von Willebrand factor; von Willebrand disease; hemophilia; substitution therapy